Hole transport materials doped to absorber film for improving the performance of the perovskite solar cells. (1st August 2019) - Wang, Qintao; Li, Haimin; Zhuang, Jia; Ma, Zhu; Wang, Fang; Zhang, Ting; Wang, Yunchao; Lei, Jianbo
Abstract: In spite of the power conversion efficiency (PCE) of the PSCs has been rapidly improved, many changes, such as defects, poor morphology and expensive hole transporte materials (HTM), are still on the way to commercial application. In this paper, CuSCN was used as the HTM to substitute the popular Spiro-OMeTAD, because of its high hole transfer capability and much lower cost. A simple, planar construction device of FTO/c-TiO2 /MAPbI3 /CuSCN/Au has been prepared, yielding a best PCE of 10.41%. To improve the stability and performance of the device, 1 mol % CuSCN was innovatively introduced into the absorber layer. The grain size of the MAPbI3 layer has increased obviously and the defects in the device were also reduced. The fast charge transportation and extraction make the short-circuit currents increased from 18.39 mA/cm 2 to 22.18 mA/cm 2 . The PCE of the CuSCN doped perovskite solar cells (PSCs) have increased 21.4% compared to the control device without added. In the meantime, the hysteresis and stability have also been improved effectively. The PCE of the CuSCN doped MAPbI3 device only dropped 28% from the initial efficiency after 500 h stored in an ambient air with temperature of 25°Cand humidity of 20%, whereas the device without CuSCN doped droped 48%. This result indicates that CuSCN has great potential as a doping to improve the morphology of perovskite films and enhance the performance of the PSCs.